The role of rhythm in religious rituals: Supporting the spirituality of Hindu-Buddhist communities in the context of eschatology - Krishnanandayani, Jyothi Devi; Chakraborty, Eshita (Life and Death: Journal of Eschatology, 2025)
Background: Music played an important role in the development of Hindu-Buddhist civilization in Indonesia, especially in spiritual life and religious rituals. Methods: This article explores how rhythm and melody became essential elements in the religious and cultural practices of the people during that time. Findings: Music not only served as entertainment, but also as a medium of connection between humans and the supernatural, creating harmony between the mortal and divine worlds. In the Hindu-Buddhist era, music was often used in religious rituals, such as temple worship ceremonies and offerings to the gods. Traditional instruments such as gamelan and gender were believed to have sacred powers that could purify the atmosphere and improve concentration in meditation. Through music, values of spirituality, harmony and devotion are embodied, reflecting the cosmic concept in Hindu-Buddhist teachings of balance between the macrocosm and microcosm. The article also discusses historical and archaeological evidence that shows the involvement of music in religious rituals, such as the reliefs in Borobudur and Prambanan Temples that depict musical instruments and religious processions. The art of music at that time not only showed a high level of aesthetics, but also became a symbol of community identity and togetherness. Conclusion: This paper discusses in depth the role of music as one of the supports of spiritual life that has helped shape the foundation of Indonesian culture and tradition to this day. Novelty/Originaloty of this article: This study uniquely highlights the sacred role of music in Hindu-Buddhist religious rituals in Indonesia, emphasizing its function as a bridge between the mortal and divine realms, which has been rarely explored in previous research.